(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2024)
Android-based digital learning media is an innovation in the developed learning media. The formulation of the problem in this study is how to develop digital learning media for the historical values of the Android-based Bumi Ayu temple. The benefits of research for students can provide an alternative to learning history, so that they can access learning whenever and wherever and for teachers to provide understanding and add insight into alternative technologies for interesting and useful learning media for history learning activities This research uses research and development (R&D) methods. The R&D method is a research method used to produce certain products and test the effectiveness of these products. From the research results of learning media testing, it can be concluded that the research results obtained are categorized as suitable for use in learning history in schools in the teaching and learning process, based on the test results, the average score of the three validators is obtained, namely media experts get an assessment of 87%, experts 88% material, validation by history teachers as media experts is 80% and material experts 80%, and student trials get 85% gains, from these results show that the developed media got a very good response and deserved to be used in history learning.